Exploring the nature of communities of inquiry in undergraduate accounting education: a systematic literature review - Marx, A.; Fouché, J. P.; Heymans, Y.; Pool, J. (South African Journal of Higher Education, 2025)
Online learning has become an integral part of higher education, and while its adoption was accelerated by the COVID-19 pandemic, it will continue to be an important mode of learning in higher education. However, research indicates that accounting students are experiencing the online learning component as a significantly bigger challenge than the face-to-face learning component. Providing a responsive online accounting learning environment requires an effective framework to assist with the design of the teaching and learning environment, facilitating optimal online learning. This article reports on a systematic literature review to determine the nature of the Community of Inquiry (CoI) framework within the context of online undergraduate accounting education. Utilising scholarly databases (Scopus, Web of Science, African Journals and EbscoHost), a literature search was conducted for the period 2012–2022, resulting in the identification of 35 articles for full-text review. The results of this review highlighted that all three presences of the CoI (social presence, cognitive presence, and teaching presence) were present. Most of the articles reported on group cohesion and affective/personal connections within social presence, and instructional design within teaching presence. Sub-themes such as triggering events within cognitive presence and direct instruction within teaching presence received the least coverage in the sampled articles. The insufficient inclusion of certain sub-themes in the presences indicated the need for further application to create a responsive online learning environment in accounting education.